Emergence of the global knowledge economy: implications for libraries and lifelong learning in Nigeria (2011)
Lifelong learning has been described as education for the knowledge economy. But indicators from international assessments suggest that some developing countries risk being marginalized in the competitive global knowledge economy because their education and training systems are described inadequate to equip learners with the skills they need for active participation. Coverage is insufficient, access is inequitable (especially in tertiary [higher] education and in employee and adult training), as education facilities are grossly inadequate and the quality of education is low. Private intervention in education has not helped matters as rote learning, exam-driven schooling, and the soaring cost of private education have long been policy concerns in most developing countries. Thus the goal of education for all has revoltingly remained elusive in many low-income countries. This paper examines the challenges that knowledge economy has posed to lifelong learning and training systems in Nigeria. It considers the implications of the knowledge economy on lifelong learning and outlines the key competencies needed for citizens to participate effectively in the knowledge economy. The paper stresses the need to strengthen public libraries in order to encourage lifelong learning in Nigeria where formal education systems are almost unaffordable and grossly inadequate. It summarizes policy options for developing viable option of lifelong learning using public libraries.